Occupational Stress and Job Performance Among University Library Professionals of North-East India - Devi, Pallabi; Lahkar, Narendra (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2021)
Objective – The present study intends to investigate the occupational stress and job performance of university library professionals in North-East India. The main objective of the study is to assess the perceived level of occupational stress among library professionals and to identify any relationship between occupational stress and library professionals’ job performance. The study also aims to study gender differences regarding perceived occupational stress and job performance among library professionals as well as examine the influence of occupational stress on perceived job performance.Methods – Descriptive survey method was used for the study. The sample population consisted of 123 library professionals from different parts of North-East India selected through convenience sampling technique. The survey consisted of a structured questionnaire divided into three sections: demographic information, self-perceived occupational stress, and self-rated job performance. Descriptive and inferential statistical techniques including frequency, mean, standard deviation, t test, correlation co-efficient, and simple linear regression analysis were used to analyze data and interpret results with the help of the statistical package SPSS version 20.Results – The findings of the study established that a majority of library professionals working in university libraries of North-East India perceived a moderate level of occupational stress. It was also determined that male and female library professionals do not differ in their perception of occupational stress (p > 0.05), while a significant mean difference was found between male and female library professionals’ perceptions towards their job performance (p < 0.05). Males scored themselves higher than females in terms of eight indicators of job performance: quality of work performance, ability to handle multiple jobs, communication skills, decision making, problem solving, technical skills, ability to perform competently under pressure, and contribution to the overall development of the library. Regarding the relationship between occupational stress and job performance, the data indicated a significant negative relationship between occupational stress and job performance (r = -0.296, p < 0.01). In addition to this, intrinsic impoverishment, under participation, low status, and poor peer relationships were some of the factors negatively affecting the job performance of library professionals.Conclusion – The present study provides an insight about how occupational stress affects job performance of library professionals working in academic libraries. The findings revealed that there exists a modest but statistically significant negative relationship between occupational stress and job performance, which implies that an increment in the level of perceived occupational stress tends to influence library professionals’ self-perception of job performance negatively.